1999
DOI: 10.1677/joe.0.1630409
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of inducible nitric oxide synthase in stress-impaired testicular steroidogenesis

Abstract: The immobilization stress induces an acute inhibition of testicular steroidogenesis that is mediated by the nitric oxide (NO) signaling pathway. Here we compared the effects of 2-h immobilization stress on in vivo and in vitro rat steroidogenesis at two time points, 0 h and 6 h after the end of the stress session. As expected, serum androgens and human chorionic gonadotropin (hCG)-stimulated progesterone and testosterone production by testicular tissue were inhibited at 0 h, and also at the 6-h time point. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…The ability of stress to inhibit reproductive function is well documented (27,28,37,38,39,40,50,55,56,64,72). A sharp decline of serum testosterone is one of the first signs of IMO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of stress to inhibit reproductive function is well documented (27,28,37,38,39,40,50,55,56,64,72). A sharp decline of serum testosterone is one of the first signs of IMO.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were raised in controlled environmental conditions (22 Ϯ 2°C; 12:12-h light-dark cycle, lights on at 7:00 A.M.) with food and water ad libitum. IMO was performed in the morning (from 0800 to 1000) by the method of Kvetnansky (41) described previously (37,39,40,50). Briefly, IMO rats were bound in the supine position to a wooden board by fixing the rat limbs by thread to the wooden board, but head motion was not limited.…”
Section: Animals and Stress Modelmentioning
confidence: 99%
“…In addition, acute restraint stress has also been shown to increase adult plasma corticosterone, and reduce plasma dihydrotestosterone and 3a-androstanediol, but not the aromatized metabolite estradiol in rats (Walf & Frye 2012). Other studies in adult rats and mice (Pomerantz & Pitelka 1998, Kostic et al 1999 have shown that acute and chronic immobilization stress can result in a decrease in serum androgen concentrations, mediated by increased nitric oxide (NO) signaling in the testes, which specifically inhibits P450c17 activity (Kostic et al 1999). It has been suggested that NO inhibits the activity of cytochrome P450 complexes by binding to the heme iron (Quaroni et al 1996) or to the sulfhydryl groups in these enzymes (Snyder et al 1996).…”
Section: Figurementioning
confidence: 98%
“…A short, 2-h session of IMO in rats produces a sharp decline of plasma T levels and blocks the LH-induced T production in hemitestis preparations incubated in vitro, and these actions have been attributed to endogenous NO activity (29). Further studies have led to the proposal that the involvement of NO in stress is due to activation of testicular inducible nitric oxide synthase (iNOS) (30,31). In addition, multiple lines of evidence support the conclusion that IMO is associated with increased NOS mRNA and protein levels in the brain cortex (36) and paraventricular nucleus (7) and in the HPA axis (27).…”
mentioning
confidence: 99%